Urgent surgery or procedures in patients taking dabigatran or warfarin: analysis of perioperative outcomes from the RE-LY trial - Douketis, James D.; Brückmann, Martina (Thrombosis research, 2016)
Background: There is concern about the management of anticoagulated patients with atrial fibrillation (AF) who require an urgent surgery/procedure, especially in those who are receiving a direct oral anticoagulant such as dabigatran. Methods: We accessed the database from RE-LY, a randomized trial comparing dabigatran (110mg and 150mg twice daily) with warfarin for stroke prevention in AF, to assess patients who had an urgent and elective surgery/procedure. We compared the risk for thromboembolism, major bleeding and mortality according to treatment allocation (dabigatran 110mg or 150mg, or warfarin) or surgery/procedure type (urgent or elective). Outcomes were assessed from day-7 to day 30 after a surgery/procedure. Results: 353 patients (2.0% of study population) had an urgent surgery/procedure and 4168 patients (23.1% of study population) had an elective surgery/procedure. In patients on dabigatran 110mg, dabigatran 150mg and warfarin who had an urgent surgery/procedure: rates of thromboembolism were 16.1%, 7.4%, and 10.5%; rates of major bleeding were 17.0%, 17.6%, and 22.9%; rates of mortality were 6.3%, 1.5%, and 2.9%, respectively (P>0.50 for all comparisons). Rates of these outcomes were multi-fold higher in patients having an urgent rather than an elective surgery/procedure (P<0.5 for all comparisons). Conclusion: In anticoagulated patients with atrial fibrillation who require an urgent surgery/procedure, the risks for thromboembolism, major bleeding and mortality did not differ depending on treatment with dabigatran or warfarin, but rates of these outcomes were multi-fold higher than in patients having an elective surgery/procedure.
Gesehen am 22.02.2019